Effects of blood flow restriction training on anthropometric and blood lipids in overweight/obese adults: Meta-analysis - Sun, Lei (Frontiers in Physiology, 2022)
Abstract: Purpose: To systematically evaluate the effects of blood flow restriction training (BFRT) on anthropometric indicators and blood lipids in overweight/obese adults. Methods：A literature search was conducted on PubMed, Web of Science, Embase, Scopus, SPORTDiscus and Cochrane Library databases to determine the final literature based on inclusion and exclusion criteria. Review Manager 5.4.1 was used to evaluate the quality of the literature based on the Cochrane bias risk assessment tool, and Stata 17.0 software was used for Meta-analysis. Results: A total of 3985 articles were screened, and 5 of the studies were included in the Meta-analysis, with a total 66 participants. In each study, subjects were measured before and after BFRT. Meta-results showed that BFRT significantly reduced BMI, lowered body weight, body fat % and waist circumference, significantly reduced total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) level, lowered triglycerides, and increased high-density lipoprotein cholesterol (HDL-C) level in overweight/obese adults. Conclusion: BFRT can be used as a safe and effective exercise prescription for personalized weight/fat loss. BFRT significantly reduces BMI by reducing body weight, body fat %, and waist circumference and has the effect of improving body composition. It also significantly reduced TC and LDL-C and tends to decrease TG and increase HDL-C in overweight/obese adults, potentially reducing the incidence of cardiovascular disease.